A Dualistic Concept of Personal Guarantee Responsibility and Its Relevancy with Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligation A Dualism Of Personal Guarantee Responsibility In Indonesia Bankruptcy Law - Liza Mashita Ramadhania (LEGAL BRIEF, 2023)
Indonesia's legal system recognizes the concept of personal guarantee, which is a promise or guarantee of an individual as a third party to fulfil the debtor's obligations. The concept of guarantee in Indonesia regulates the roles and responsibilities of personal guarantees if the debtor cannot pay his debts. However, the problem is a dualism in theory or approach to personal guarantee responsibility, especially in carrying out debt collection in the debt settlement process in Bankruptcy and Suspension of Debt Payment Obligations ("PKPU"). This dualism exists in the approach to justify actions for the creditor in determining who can be claimed to fulfil debt payment obligations - the debtor or personal guarantor. The main purpose of this journal is to analyze the existence of dualism problems in the concept of responsibility in personal guarantees and how to address the issues. In this journal, the author uses normative juridical research methods, which can be analyzed with conceptual and statutory approaches. This journal addresses an analysis that there are still inconsistencies in Indonesian legal practice in determining responsibility for the implementation of debt obligations, especially in deciding bankruptcy cases in Indonesia. Regarding whose debt responsibility is, there is still a dual approach, namely whether to use the "guarantor is always a guarantor" approach or the "guarantor is the debtor" approach. This journal concludes that there is a legal vacuum to resolve these circumstances. Regardless of the dualism of these circumstances, the author argues that it is necessary to unify the concept of responsibility for personal guarantees to provide legal certainty, especially concerning the implementation of debt collection in the bankruptcy process and at the time of PKPU.The dualism of personal guarantee theory has indicated that it is urgently needed to unify the concept of personal guarantee to provide legal certainty, especially concerning the implementation of debt collection in the process of settlement of debts in bankruptcy and at Suspension of Debt Repayment Obligation (Penundaan Kewajiban Pembayaran Utang/PKPU), where the creditor must determine who can be claimed to fulfill the debt payment obligations. In this paper, the author seeks who is responsible to pay the debt when there is a personal guarantor to guarantee the debtor, and also to examine the debt settlement process through PKPU or bankruptcy.